Pengaruh Gender, Pengalaman, Keahlian, Situasi Audit Dan Etika Terhadap Skeptisisme Profesional Auditor - Rafli Raynaldi; Mayar Afriyenti (Universitas Negeri Padang, 2020)
This study aims to determine the effect of Gender, Experience, Expertise, Audit Situation, and Ethics on the auditor’s professional skepticism. The population in this study is the auditor at the Public Accountant Office in the City of Padang. The population in Padang City is 7 Public Accountants with 45 auditors. The sample in this study uses the total sampling method because the total population is less than 100, then the entire populaton is sampled. The data used are primary data. Data collection techniques are used by means of Library Studies and Field Research. Data analysis method used is multiple linear regression. The results of this study indicate that gender affects auditor professuonal skepticism, expertise has a significant effect on the accuracy of auditor opinion, the audit situation has a effect on the accuracy of auditor opinion, the audit siuation has a positive effect on auditor skepticism and ethics has a significant effect on auditor skepticism.